Dancing backwards in high heels: Female professors experience more work demands and special favor requests, particularly from academically entitled students - El-Alayli, Amani; Hansen-Brown, Ashley A.; Ceynar, Michelle (Sex Roles, 2018)
Although the number of U.S. female professors has risen steadily in recent years, female professors are still subject to different student expectations and treatment. Students continue to perceive and expect female professors to be more nurturing than male professors are. We examined whether students may consequently request more special favors from female professors. In a survey of professors (n = 88) across the United States, Study 1 found that female (versus male) professors reported getting more requests for standard work demands, special favors, and friendship behaviors, with the latter two mediating the professor gender effect on professors’ self-reported emotional labor. Study 2 utilized an experimental design using a fictitious female or male professor, with college student participants (n = 121) responding to a scenario in which a special favor request might be made of the professor. The results indicated that academically entitled students (i.e., those who feel deserving of success in college regardless of effort/performance) had stronger expectations that a female (versus male) professor would grant their special favor requests. Those expectations consequently increased students’ likelihood of making the requests and of exhibiting negative emotional and behavioral reactions to having those requests denied. This work highlights the extra burdens felt by female professors. We discuss possible moderators of these effects as well as the importance of developing strategies for preventing them. © 2017, Springer Science+Business Media, LLC, part of Springer Nature.
Keywords: amériques; approches et analyses; discipline; femmes professeures; milieux universitaires; projet charge mentale; psychologie; psychologie sociale; rapports sociaux de sexe; régions géographiques; sciences humaines; stéréotypes de genre; thématiques; travail; travail émotionnel; états-unis

The Role of Gender and Ethnicity in Perceptions of Rape and Its Aftereffects - Schneider, Lawrence J.; Mori, Lisa T.; Lambert, Paul L.; Wong, Anna O. (Sex Roles : A Journal of Research, 2009)
Caucasian-, Hispanic-, and Asian-American male and female students (n = 764) attending a California (USA) public university reported their perceptions of sexual assault. After reading a rape vignette, participants gave their impressions of the victim; estimated time needed for recovery and treatment; and recommended a sentence for the assailant. Half of the sample received information regarding state sentencing guidelines. Relative to female participants, males perceived the victim as more responsible. Caucasian-American males had stronger reservation about the victim’s judgment. Males were less inclined to assign blame than were females. Ethnicity was the only factor influencing perceptions of recovery. Ethnicity and sentencing guidelines, but not gender, impacted imprisonment decisions. Issues impeding a unified theoretical understanding of perceptions of rape victims were considered.
Keywords: 2000 à aujourd'hui; 2000-2009; amériques; approches et analyses; californie; cours; discipline; intersectionnalité; perception; premier cycle; psychologie; périodes historiques; rapports sociaux de sexe; ressource en ligne; régions géographiques; santé; sciences humaines; sex2283; thématiques; viol; violences; états-unis

Sexual Attitudes and Double Standards: A Literature Review Focusing on Participant Gender and Ethnic Background - Fugère, Madeleine A.; Escoto, Carlos; Cousins, Alita J.; Riggs, Matt L.; Haerich, Paul (Sexuality & Culture : An Interdisciplinary Quarterly, 2008)
We conducted a review of literature regarding sexual attitudes and double standards, focusing on participant gender and ethnic background. We found that men had more permissive sexual attitudes than women, and that African Americans had the most permissive sexual attitudes, followed by White Americans, then by Hispanic Americans and Asian Americans. The literature regarding sexual double standards was mixed; some studies showed evidence of continued sexual double standards and some studies showed the absence of sexual double standards. In some studies, men were more likely to endorse the sexual double standard than women. We found only one article addressing sexual double standards using ethnic background as a quasi-independent variable; this research revealed that non-North American (Russian and Japanese) samples were more likely to endorse the traditional double standard, that sex is more acceptable for men than for women.
Keywords: 1900-1999; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; amériques; approches et analyses; asie; cours; discipline; europe; japon; premier cycle; psychologie; périodes historiques; rapports sociaux de sexe; ressource en ligne; russie; régions géographiques; sciences humaines; sciences sociales; sex2283; sexisme; sexologie; sexualité; systèmes d'oppressions; thématiques; états-unis

Woman: An intimate geography - Angier, Natalie (Anchor Books, 2000)
Woman is a fascinating, fact-filled guide that covers everything from organs to orgasms, hormones to hysterectomies. With her characteristic clarity, insight, and sheer exuberance of language, bestselling author Natalie Angier cuts through the still-prevalent myths and misinformation surrounding the female body, that most enigmatic of evolutionary masterpieces. With a witty and assured narrative, and a reader-friendly dose of science, Woman is an essential and engaging resource for all time.
Keywords: amériques; approches et analyses; biologie; corps; cours; différence des sexes; discipline; fem1000; médecine; premier cycle; psychologie; rapports sociaux de sexe; régions géographiques; santé; sciences; sciences humaines; stéréotypes; thématiques; états-unis